International workshop on natural resources - Ruiz Cancino, Enrique; Universidad Autónoma de Tamaulipas (Libros UAT, 2019)
The PROMEP Network of Academic Bodies "Systematics and ecology in forest communities and crops" began its activities in October 2008. Its objectives are to expand taxonomic and ecological knowledge of selected families of animals and fungi, and to disseminate their results at events. and scientific publications.